Ventilação não invasiva versus espirometria de incentivo na prevenção de complicações pulmonares no pós-operatório de revascularização do miocárdio - Alves, Fernanda Menezes de Siqueira Santana (2017)
Introduction: Coronary Artery Disease (CAD) is considered as one of the presentation forms of cardiovascular disease. Myocardial revascularization surgery (MRS) is one of the possible interventions for its treatment; however, it is an invasive procedure with postoperative complications. Objectives: To identify the pulmonary complications after MRS with extracorporeal circulation, determining the efficacy of non-invasive ventilation (NIV) in comparison with incentive spirometry (IS) in the postoperative management and to update knowledge related to the respiratory and motor Physiotherapy in pre and post MRS. Materials and Methods: A total of 105 patients were randomized into two groups (G0 - IS and G1 - CPAP). The blood gas values, chest X-ray and respiratory muscle strength were assessed before the pre, first and third postoperative day according to the incidence of pulmonary complications presented. Results: The complications presented in both groups were hypoxemia, atelectasis, pleural effusion, pneumonia and lung congestion, proportionately distributed with no statistically significant correlation with the technique used in the postoperative period. The maximum inspiratory pressure (MIP) was reduced in both groups in the pre and the first day after surgery, carrying on up to the third day after surgery only in the group 0. The maximum expiratory pressure (MEP) remained significantly reduced in both groups postoperatively when compared to predicted values. Conclusion: Respiratory physical therapy modalities used were effective in maintaining inspiratory muscle strength, however, no statistically significant difference in the proportion of expressed pulmonary complications between the groups, inferring non superiority of NIV technique compared to IS in the reversal of pulmonary complications post MRS. Further studies accomplished with stricter methodology, greater number of subjects studied and technical standardization are necessary. Moreover, to determine the appropriate method or protocol for restoring pulmonary and physical condition of these patients postoperatively.